Notary Authority in the Making of Minutes Deed of Electronic General Meeting of Shareholders (E-GMS) For Public Company based on the Principle of Legal Certainty - Rizky Olvia, Ghea; Saprudin, Saprudin (Notary Law Journal, 2024)
This research analyzes the authority of notaries in creating minutes deeds for e-GMS of Public Companies, based on the principle of legal certainty. The research uses normative juridical methods, employing a conceptual approach to laws, regulations, theories, and expert opinions to address the issues raised. The findings indicate that the stipulations in article 12 of POJK 16/2020, which require that e-GMS minutes be made in the form of a notarial deed without signatures from the GMS participants, align with article 46 of UU-JN. This alignment provides legal certainty regarding the Notary's authority in conducting e-GMS. Despite conflicts between POJK 16/2020 and UU-PT, POJK 16/2020 is considered a specific provision (lex specialis) through UU-4/2023, while UU-PT is a general provision (lex generalis). Article 8 paragraph (1) letter b of POJK 16/2020 aligns with article 16 paragraph (1) of UUJN-P, emphasizing the necessity of physical presence for notaries, appearing parties, and witnesses in notarial deeds. Without clear "specific conditions" as mentioned in article 9 of POJK 16/2020, the requirement for notarial deeds must follow the Notary Law. If the physical presence requirement is unmet, the deed only holds the evidentiary strength of an underhand deed as per article 16 paragraph (9) of UUJN-P. For supervision and law enforcement purposes, the Capital Market Notary must state in the deed that the submission of electronic data by the e-GMS Provider does not absolve its responsibility in ensuring the validity of the electronic data in the implementation of the e-GMS for Public Companies